2013
DOI: 10.1007/s40195-012-0231-0
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion mechanism of corrosion-resistant steel developed for bottom plate of cargo oil tanks

Abstract: A new type of corrosion-resistant steel consisting of ferrite and bainite phases was developed for cargo oil tanks of crude oil tankers. The corrosion rate of this new steel was 0.22 mm/a, which was equivalent to ca. 1/5 of the criterion (≤ 1 mm/a) for corrosion-resistant steels. The composition and element distribution of the corrosion products were investigated by micro-Raman spectrometry and energy dispersive spectrometer. The results demonstrated that the corrosion product was composed of α-FeOOH, Fe 3 O 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The increasing global energy demand continues to push oil companies into deeper and deeper waters in search of economically recoverable reserves of oil and gas [1][2][3]. However, for the marine structures, the effects of the elements and applied loads potentially result in unsafe conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing global energy demand continues to push oil companies into deeper and deeper waters in search of economically recoverable reserves of oil and gas [1][2][3]. However, for the marine structures, the effects of the elements and applied loads potentially result in unsafe conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] However, very few studies on the corrosion behavior of COT steel have been reported. [13][14][15] The evaluation methods of corrosion resistance have been widely concerned. Weigh loss measurement is the most direct and reliable method but time consuming and information limited, therefore the corrosion resistance has been investigated by simulated and accelerated corrosion tests.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al . developed new corrosion resistant steel which was composed of ferrite and bainite for crude oil tank. The composition and element distribution of corrosion products were studied by micro Raman spectroscopy and energy dispersive spectrometer.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray diffraction analysis of the corrosion products of these two materials showed that the corrosion products were mainly CaCO 3 and FeS, among others. Sun et al [13] developed new corrosion resistant steel Table 2. SEM images of coupon surfaces corroded by different sedimentary liquids at ambient temperature.…”
Section: Static Coupon Testmentioning
confidence: 99%